Pengaruh Literasi Keuangan Locus Of Control, Gaya Hidup Hedonisme, Dan Efikasi Diri Keuangan Terhadap Perilaku Pengelolaan Keuangan - Monica, Massiva Virginia; Harahap, Aderina; Yuliana, -; Suheriyatmono, -; Luthfi, Muhammad (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2025)
This Study aims to determine the effect of financial literacy, locus of control, hedonistic lifestyle, and financial self efficacy on financial management behavior. This study uses a quantitative approach with datacollected through questionaires involving 100 respondents using purposive sampling, who are generation Z who transact usingShopeepay in Bandar Lampung. The analysis method used is multiple linier regression. The result show that Financial Literacy, Hedonistic Lifestyle, and Financial Self Efficacy have a significant partial effect on Financial manajemen Behavior, while the Locus of Control variable does not havea a significant effect on Financial Manajemen Behavior.  Simultaneously, all variable have an effect on Financial Management Behavior.